Why do avian responses to change in Arctic green‐up vary? - Eveling A. Tavera; David B. Lank; David C. Douglas; Brett K. Sandercock; Richard B. Lanctot; Niels M. Schmidt; Jeroen Reneerkens; David H. Ward; Joël Bêty; Eunbi Kwon; Nicolas Lecomte; Cheri Gratto‐Trevor; et al. (Global Change Biology, 2024)
Global climate change has altered the timing of seasonal events (i.e., phenology) for a diverse range of biota. Within and among species, however, the degree to which alterations in phenology match climate variability differ substantially. To better understand factors driving these differences, we evaluated variation in timing of nesting of eight Arctic‐breeding shorebird species at 18 sites over a 23‐year period. We used the Normalized Difference Vegetation Index as a proxy to determine the start of spring (SOS) growing season and quantified relationships between SOS and nest initiation dates as a measure of phenological responsiveness. Among species, we tested four life history traits (migration distance, seasonal timing of breeding, female body mass, expected female reproductive effort) as species‐level predictors of responsiveness. For one species (Semipalmated Sandpiper), we also evaluated whether responsiveness varied across sites. Although no species in our study completely tracked annual variation in SOS, phenological responses were strongest for Western Sandpipers, Pectoral Sandpipers, and Red Phalaropes. Migration distance was the strongest additional predictor of responsiveness, with longer‐distance migrant species generally tracking variation in SOS more closely than species that migrate shorter distances. Semipalmated Sandpipers are a widely distributed species, but adjustments in timing of nesting relative to variability in SOS did not vary across sites, suggesting that different breeding populations of this species were equally responsive to climate cues despite differing migration strategies. Our results unexpectedly show that long‐distance migrants are more sensitive to local environmental conditions, which may help them to adapt to ongoing changes in climate.

Biogeography of Beringian fishes after the molecular revolution and into the post-genomics era - Matthew A. Campbell; Randy J. Brown; Kevin M. Fraley; Dmitry V. Politov; J. Andrés López; Martin D. Robards (Reviews in Fish Biology and Fisheries, 2024)
Significant progress in our knowledge of Beringian biodiversity and in the technologies available for biodiversity research has been made in the several decades since a comprehensive biogeographic synthesis of Beringian freshwater fishes was compiled and published in 1986. Further, the fish fauna of Beringia and, more broadly, of high latitude freshwater systems of the northern hemisphere face some of the most intense well documented effects of global climate change. Here we synthesize current understanding of how the dynamic spatial and ecological landscapes of Pleistocene glaciations have shaped the distribution of taxonomic and genetic diversity in fish faunas of Beringia. Through a more complete integration of knowledge obtained in studies of fishes in Russian drainages, we aimed to identify promising strategies to test alternative biogeographic hypotheses on the roles played by the Bering land bridge, paleorivers and glacial history in intercontinental faunal movement. We focus on freshwater fishes of the Bering Strait region, which live in an environment that is premised on extreme instability and profound changes in long-term connectivity for fishes and offers opportunities to assess long-term evolutionary trends in both speciation and life history variation. Such information is critical for both our scientific understanding of evolutionary processes in fishes and valuable for those tasked with the challenges of management and conservation of natural resources in this expansive, dynamic and remote region. We provide an overview of Beringian freshwater ichthyofauna and examine genetic differentiation among population units within these lineages. We also examine evidence for how long population units have been separated based on historic glacially-related separations and the more recent marine barrier of the Bering Strait that constrains freshwater or diadromous species based on their ability to disperse in salt water. Our review concludes on how Arctic and sub-Arctic fishes may adapt and persist in their dynamic environment considering low genetic diversity, the role of adaptive introgression, and epigenetic variation. We find that Beringian fishes may poorly fit traditional taxonomic categories and the designation of conservation units below the species level may be of great practical application. Furthermore, as hybridization is documented to increase in the Arctic, the use of this process for ecological monitoring may also be of high utility with Beringian fishes.

Factors influencing mercury exposure in Arctic-breeding shorebirds - Marie Perkins; Iain J. Stenhouse; Richard B. Lanctot; Stephen Brown; Joël Bêty; Megan Boldenow; Jenny Cunningham; Willow English; River Gates; H. Grant Gilchrist; Marie-Andrée Giroux; Kirsten Grond; et al. (Ecotoxicology, 2023)

Wolverines (Gulo gulo) in the Arctic: Revisiting distribution and identifying research and conservation priorities amid rapid environmental change - Thomas W. Glass; Audrey J. Magoun; Martin D. Robards; Knut Kielland (Polar Biology, 2022)

Freshwater input and ocean connectivity affect habitats and trophic ecology of fishes in Arctic coastal lagoons - Kevin M. Fraley; Martin D. Robards; Matthew C. Rogers; Johanna Vollenweider; Beatrice Smith; Alex Whiting; Tahzay Jones (Polar Biology, 2021)

Permafrost ice caves: an unrecognized microhabitat for Arctic wildlife - Thomas W. Glass; Greg A. Breed; Go Iwahana; Matthew C. Kynoch; Martin D. Robards; Cory T. Williams; Knut Kielland (Ecology, 2021)

Spatiotemporally variable snow properties drive habitat use of an Arctic mesopredator - Thomas W. Glass; Greg A. Breed; Glen E. Liston; Adele K. Reinking; Martin D. Robards; Knut Kielland (Oecologia, 2021)

Spatial Management Measures Alter Vessel Behavior in the Aleutian Archipelago - Benjamin K. Sullender; Kelly Kapsar; Aaron Poe; Martin Robards (Frontiers in Marine Science, 2021)
The Aleutian Archipelago and surrounding waters have enormous ecological, cultural, and commercial significance. As one of the shortest routes between North American and Asian ports, the North Pacific Great Circle Route, which crosses through the Aleutian Archipelago, is traveled by thousands of large cargo ships and tanker vessels every year. To reduce maritime risks and enhance navigational safety, the International Maritime Organization built upon earlier offshore routing efforts by designating five Areas To Be Avoided (ATBAs) in the Aleutian Islands in 2016. The ATBAs are designed to keep large vessels at least 50 nautical miles (93 km) from shore unless calling at a local port or transiting an authorized pass between islands. However, very few studies have examined the effectiveness of ATBAs as a mechanism for changing vessel behavior and thereby reducing the ecological impacts of maritime commerce. In this study, we use 4 years of satellite-based vessel tracking data to assess the effectiveness of the Aleutian ATBAs since their implementation in 2016. We determined whether vessels transiting the North Pacific Great Circle Route changed behavior after ATBA implementation, both in terms of overall route selection and in terms of compliance with each ATBA boundary. We found a total of 2,252 unique tankers and cargo vessels >400 gross tons transited the study region, completing a total of 8,794 voyages. To quantify routing changes of individual vessels, we analyzed the 767 vessels that transited the study region both before and after implementation. The percentage of voyages transiting through the boundaries of what would become ATBAs decreased from 76.3% in 2014–2015 (prior to ATBA designation) to 11.8% in 2016–2017 (after implementation). All five Aleutian ATBAs had significant increases in compliance, with the West ATBA showing the most dramatic increase, from 32.1% to 95.0%. We discuss the framework for ATBA enforcement and highlight the value of local institutional capacity for real-time monitoring. Overall, our results indicate that ATBAs represent a viable strategy for risk mitigation in sensitive ecological areas and that through monitoring, spatial protections influence vessel route decisions on multiple spatial scales.

Seasonal variation in Arctic marine mammal acoustic detection in the northern Bering Sea - Emily Chou; Ricardo Antunes; Stephanie Sardelis; Kathleen M. Stafford; Leigh West; Christopher Spagnoli; Brandon L. Southall; Martin Robards; Howard C. Rosenbaum (Marine Mammal Science, 2020)
Declines in Arctic sea ice cover are influencing the distribution of protected endemic marine mammals, many of which are important for local Indigenous Peoples, and increasing the presence of potentially disruptive industrial activities. Due to increasing conservation concerns, we conducted the first year‐round acoustic monitoring of waters off Gambell and Savoonga (St. Lawrence Island, Alaska), and in the Bering Strait to quantify vocalizing presence of bowhead whales, belugas, walruses, bearded seals, and ribbon seals. Bottom‐mounted archival acoustic recorders collected data for up to 10 months per deployment between 2012 and 2016. Spectrograms were analyzed for species‐typical vocalizations, and daily detection rates and presence/absence were calculated. Generalized additive models were used to model call presence as a function of time‐of‐year, sea surface temperature, and sea ice concentration. We identified seasonality in call presence for all species, corroborating previous acoustic and distribution studies, and identified finer‐scale spatiotemporal distribution via occurrence of call presence between different monitoring sites. Time‐of‐year was the strongest significant effect on call presence for all species. These data provide important information on Arctic endemic species' spatiotemporal distributions in biologically and culturally important areas within a rapidly changing Arctic region.

The risk of rodent introductions from shipwrecks to seabirds on Aleutian and Bering Sea islands - Martin Renner; Eric Nelson; Jordan Watson; Alan Haynie; Aaron Poe; Martin Robards; Steve C. Hess (Biological Invasions, 2018)

Assessing development impacts on Arctic nesting birds using real and artificial nests - Rebecca Bentzen; Stephen Dinsmore; Joseph Liebezeit; Martin Robards; Bill Streever; Steve Zack (Polar Biology, 2017)

Distribution and spawning dynamics of capelin ( Mallotus villosus ) in Glacier Bay, Alaska: a cold water refugium - MAYUMI L. ARIMITSU; JOHN F. PIATT; MICHAEL A. LITZOW; ALISA A. ABOOKIRE; MARC D. ROMANO; MARTIN D. ROBARDS (Fisheries Oceanography, 2008)
Pacific capelin ( Mallotus villosus ) populations declined dramatically in the Northeastern Pacific following ocean warming after the regime shift of 1977, but little is known about the cause of the decline or the functional relationships between capelin and their environment. We assessed the distribution and abundance of spawning, non‐spawning adult and larval capelin in Glacier Bay, an estuarine fjord system in southeastern Alaska. We used principal components analysis to analyze midwater trawl and beach seine data collected between 1999 and 2004 with respect to oceanographic data and other measures of physical habitat including proximity to tidewater glaciers and potential spawning habitat. Both spawning and non‐spawning adult Pacific capelin were more likely to occur in areas closest to tidewater glaciers, and those areas were distinguished by lower temperature, higher turbidity, higher dissolved oxygen and lower chlorophyll a levels when compared with other areas of the bay. The distribution of larval Pacific capelin was not sensitive to glacial influence. Pre‐spawning females collected farther from tidewater glaciers were at a lower maturity state than those sampled closer to tidewater glaciers, and the geographic variation in the onset of spawning is likely the result of differences in the marine habitat among sub‐areas of Glacier Bay. Proximity to cold water in Glacier Bay may have provided a refuge for capelin during the recent warm years in the Gulf of Alaska.

Global constraints on rural fishing communities: whose resilience is it anyway? - Martin D Robards; Joshua A Greenberg (Fish and Fisheries, 2007)
Sustaining natural resources is regarded as an important component of ecological resilience and commonly assumed to be of similar importance to social and economic vitality for resource‐dependent communities. However, communities may be prevented from benefiting from healthy local resources due to constrained economic or political opportunities. In the case of Alaskan wild salmon, the fisheries are in crisis due to declining economic revenues driven by the proliferation of reliable and increasingly high‐quality products from fish farms around the world. This stands in contrast with many of the world's wild‐capture fisheries where diminished biological abundance has led to fishery collapse. Furthermore, increasing efficiency of salmon farm production, globalization, and dynamic consumer preferences, suggests that the wild salmon industry will continue to be challenged by the adaptability, price and quality of farmed salmon. Conventional responses to reduced revenues by the wild‐capture industry have been to increase economic efficiency through implementing a range of entry entitlement and quota allocation schemes. However, while these mechanisms may improve economic efficiency at a broad scale, they may not benefit local community interests, and in Alaska have precipitated declines in local ownership of the fishery. To be viable, economic efficiency remains a relevant consideration, but in a directionally changing environment (biological, social or economic), communities unable to procure livelihoods from their local resources (through access or value) are likely to seek alternative economic opportunities. The adopted strategies, although logical for communities seeking viability through transformation in a changing world, may not be conducive to resilience of a ‘fishing community’ or the sustainability of their wild fish resources. We use a theoretically grounded systems approach and data from Alaska's Bristol Bay salmon fishery to demonstrate feedbacks between global preferences towards salmon and the trade‐offs inherent when managing for the resilience of wild salmon populations and human communities at different scales.

Growth and Abundance of Pacific Sand Lance, Ammodytes hexapterus, under differing Oceanographic Regimes - Martin D. Robards; George A. Rose; John F. Piatt (Environmental Biology of Fishes, 2002)